Gagliardo–Nirenberg type inequalities for smoothness spaces related to Morrey spaces over n-dimensional torus - Balgimbayeva, Sh.A.; Janabilova, A.K. (Karagandy University of the name of acad. E.A. Buketov, 2025)
In the paper, the Gagliardo–Nirenberg type inequalities for smoothness spaces Bs p q (Tn) of Nikol’skii–Besov type and spaces Fs p q (Tn) (Tn) of Lizorkin–Triebel type both related to Morrey spaces over n-dimensional torus for some range of the parameters s; p; q; were proved. These spaces are natural analogues of the spaces Bs pq (Rn) and Fs pq (Rn) in the case of multidimensional torus Tn. The main results of the article are two theorems, each of which proves the Gagliardo–Nirenberg type inequality for the Lizorkin–Triebel type spaces or the Nikol’skii–Besov type spaces respectively.
Keywords: 41A55; 41A63; 42A35; 2020 Mathematics Subject Classification: 42A35, 41A63, 41A55; 2020 Mathematics Subject Classification; Gagliardo–Nirenberg type inequalities; multidimensional torus; Nikol’skii–Besov/Lizorkin–Triebel smoothness spaces related to Morrey space